'Real time' genetic manipulation: a new tool for ecological field studies. (6th September 2013) - Schäfer, Martin; Brütting, Christoph; Gase, Klaus; Reichelt, Michael; Baldwin, Ian; Meldau, Stefan
Summary Field experiments with transgenic plants often reveal the functional significance of genetic traits that are important for the performance of the plants in their natural environments. Until now, only constitutive overexpression, ectopic expression and gene silencing methods have been used to analyze gene‐related phenotypes in natural habitats. These methods do not allow sufficient control over gene expression for the study of ecological interactions in real time, of genetic traits that play essential roles in development, or of dose‐dependent effects. We applied the sensitive dexamethasone (DEX)‐inducible pOp6/LhGR expression system to the ecological model plant Nicotiana attenuata and established a lanolin‐based DEX application method to facilitate ectopic gene expression and RNA interference‐mediated gene silencing in the field and under challenging conditions (e.g. high temperature, wind and UV radiation). Fully established field‐grown plants were used to silence phytoene desaturase and thereby cause photobleaching only in specific plant sectors, and to activate expression of the cytokinin (CK) biosynthesis gene isopentenyl transferase (ipt). We used ipt expression to analyze the role of CKs in both the glasshouse and the field to understand resistance to the native herbivore Tupiocoris notatus, which attacks plants at small spatial scales. By spatially restricting ipt expression and elevating CK levels in single leaves, damage by T. notatus increased, demonstrating the role of CKs in this plant–herbivore interaction at a small scale. As the arena of most ecological interactions is highly constrained in time and space, these tools will advance the genetic analysis of dynamic traits that matter for plant performance in nature.